Keadilan Sosial Dalam Ekonomi Syari'ah Melalui Tafsir Surat Ar-Ra'd Ayat 11 Tentang Perubahan Sosial dan Ekonomi Umat - Malasyi, Sibral; Tarigan, Azhari Akmal; Syahreza, Rahmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam (IAI) Al-Aziziyah Samalanga, 2024)
This paper discusses the application of sosial justice principles in Islamic economics through the interpretation of Surah Ar-Ra'd verse 11, highlighting its relevance to social and economic transformation within the Muslim community. The verse emphasizes that significant societal changes can only occur when individuals and communities first change themselves. This underscores the importance of internal awareness as a foundation for broader social change. In Islamic economics, social justice serves as a central pillar, encompassing fair wealth distribution, the prohibition of economic exploitation (riba, gharar, and maysir), and community empowerment through zakat, waqf, and infaq. The analysis, based on the library research method, reveals a strong interconnection between social and economic transformation. Changes in societal values and mindsets drive the establishment of a more equitable economic system, while just economic policies accelerate inclusive social change. The application of social justice principles remains relevant in the modern era, addressing challenges of economic and social inequality. Reforms in the Sharia-based financial system, Islamic fiscal policies, and empowerment through Islamic economic education and Sharia-based SMEs are concrete steps toward reducing social disparities. A synergy between the state and society is essential to realize social justice in Islamic economics. The state plays a role in creating supportive regulations, while society actively contributes to their implementation. Thus, the interpretation of Surah Ar-Ra'd verse 11 provides both theological and practical foundations for establishing a just and sustainable economic system. Makalah ini membahas penerapan prinsip keadilan sosial dalam ekonomi syari'ah melalui tafsir Surat Ar-Ra'd Ayat 11, dengan menyoroti keterkaitannya dengan perubahan sosial dan ekonomi umat. Ayat ini menegaskan bahwa perubahan besar dalam masyarakat hanya dapat terjadi apabila individu dan masyarakat terlebih dahulu mengubah diri mereka sendiri. Hal ini menegaskan pentingnya kesadaran internal sebagai dasar perubahan sosial yang lebih luas. Dalam ekonomi syari'ah, keadilan sosial menjadi pilar utama, mencakup distribusi kekayaan yang adil, larangan eksploitasi ekonomi (riba, gharar, dan maysir), serta pemberdayaan umat melalui zakat, wakaf, dan infak. Analisis berbasis metode library research ini menunjukkan adanya hubungan erat antara perubahan sosial dan ekonomi. Perubahan nilai dan pola pikir masyarakat mendorong terciptanya sistem ekonomi yang lebih adil, sementara kebijakan ekonomi yang berkeadilan mempercepat perubahan sosial yang inklusif. Penerapan prinsip keadilan sosial tetap relevan di era modern dalam menghadapi tantangan ketimpangan sosial dan ekonomi. Reformasi sistem keuangan syari'ah, kebijakan fiskal Islami, serta pemberdayaan melalui pendidikan ekonomi syari'ah dan UMKM berbasis syari'ah menjadi langkah konkret mengurangi kesenjangan sosial. Sinergi antara negara dan masyarakat diperlukan untuk mewujudkan keadilan sosial dalam ekonomi syari'ah. Negara berperan dalam menciptakan regulasi yang mendukung, sementara masyarakat berkontribusi aktif mendukung implementasinya. Dengan demikian, tafsir Surat Ar-Ra'd Ayat 11 memberikan landasan teologis dan praktis untuk menciptakan sistem ekonomi yang berkeadilan dan berkelanjutan.